1997
DOI: 10.1002/hep.510250611
|View full text |Cite
|
Sign up to set email alerts
|

The successful treatment of symptomatic, refractory hepatic hydrothorax with transjugular intrahepatic portosystemic shunt

Abstract: Management of hepatic hydrothorax is difficult and oftenHepatic hydrothorax is a rare complication of portal results in iatrogenic complications. Repeated thoracentesis, hypertension. Conservative therapy may be successful chest tube thoracostomy, pleurodesis, and peritoneovenous but refractory hepatic hydrothorax is not uncommon.shunt have been used with varying degrees of success. HowManagement of refractory hydrothorax is usually inefever, there have been many reports of failure and complicafective and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
103
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(112 citation statements)
references
References 10 publications
3
103
0
3
Order By: Relevance
“…Jeffries et al [9] reported one response lasting greater than 2 years. In Table 3 Reports of chest tubes placed for hepatic hydrothorax N Successful removal TIPS Complications Mortality addition, short-term mortality in the series in which therapeutic TIPS was performed is \30% [23,24]. This study is limited by its design.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Jeffries et al [9] reported one response lasting greater than 2 years. In Table 3 Reports of chest tubes placed for hepatic hydrothorax N Successful removal TIPS Complications Mortality addition, short-term mortality in the series in which therapeutic TIPS was performed is \30% [23,24]. This study is limited by its design.…”
Section: Discussionmentioning
confidence: 97%
“…TIPS has been shown to be effective in preventing reaccumulation of pleural effusion in patients who are refractory to diuretics and in decreasing mortality. Clinical and radiographic improvement in hydrothorax has been documented in up to 68% of patients undergoing TIPS [8,[22][23][24]. Jeffries et al [9] reported one response lasting greater than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…10,22 Currently, information on the use of TIPS for refractory hepatic hydrothorax is limited to several small series. 14,15 In the earliest series, a clinical benefit was demonstrated in all 5 treated subjects.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12][13] In addition, several reports of the beneficial effect of TIPS in treatment of patients with refractory hepatic hydrothorax have recently been published. 14,15 In one series, a beneficial response was observed in 79% of treated patients, but substantial early and late mortality was also encountered. 15 The aim of this longitudinal study was to report on the long-term efficacy and safety of TIPS for refractory hepatic hydrothorax in 12 consecutive subjects treated at a single center.…”
mentioning
confidence: 96%
“…Though not as effective as replacing shunt, urokinase has been reported to be able to restore shunt patency [8]. Other treatment options for recurrent hydrothorax besides thoracentesis are transjugular intrahepatic portosystemic shunt (TIPS), pleurodesis, and thoracoscopic surgery to repair the diaphragmatic defect [9,10]. In addition, portal venous thrombosis was also noted (b, solid white arrow)…”
mentioning
confidence: 99%